Ethical and Regulatory Challenges for Contract Research Organizations Conducting (Outsourced) Clinical Research in Sub-Saharan Africa with a Case Study of Cameroon - Fokunang, Charles Ntungwen; Tembe-Fokunang, Estella Achick; Ngounou, Marceline Djuidje; Ngono, Basile; Mantsana, Innocente; Duclaire, Pasteur Sap Jacques; Jean, Mgr Etoundi; Eymard, Mpah Wanga Julien; Illiasou, Mfochive Njindam; Tiwoda, Christie; Ateba, Francis Ndongo; Tiabou, Tchinda; et al. (Journal of Advances in Medical and Pharmaceutical Sciences, 2025)
Introduction: Contract Research Organizations (CROs), Clinical Research Centers/Networks and private research institutions play an important role in the clinical research process, especially in the drug discovery and development process. They act as essential partners for pharmaceutical drug delivery/development and biotech companies. Over the last few decades, the demand for outsourcing of clinical research by pharmaceutical companies has increased, with the market for CRO and private research institutional services growing significantly. This trend has been driven by a need for increased productivity and efficiency to meet the increasing research and development costs, as well as the complexities associated with modern drug development. Statement of objective: This study has an objective to establish CROs with known recognition in sub Saharan Africa. Special emphasis on Cameroon institutions regulating and conduct clinical research. Methodology: Historically, drug discovery services were predominantly conducted in-house, safeguarding intellectual property and close collaboration with internal teams. However, the competitive nature of the sector has motivated pharmaceutical companies to adopt an outsourcing model, allowing them to decentralize, outsourced and exploit specialized expertise and technologies offered by the CROs. These partnerships enable drug developers to accelerate the identification and validation of promising drug candidates through streamlined pre-clinical and clinical trial processes. This is systematic research findings that we conducted a systematic search of the source documents from organizations, access to websites and google search to assemble our information, e-data information system. The systematic search gave us information on the contract organizations with online visibility. Vital information from annual reports, web information system management of the different organizations were accessible for easy navigations. Information on laws governing clinical research and major regulators in Cameroon. Results: Through a systematic online search contract research organization operating in Cameroon and Sub Saharan Africa that were available and accessible on line were identified. The list was not exhaustive as some CROs may be in existence but we could not have access to their activities and home page for enough visibility online. The organizations and CROs operating in Cameroon have been well illustrated. The laws and regulations governing clinical research in Cameroon has been well illustrated. It was observed that CROs face multiple challenges. The Contract Research Organization (CRO) are faced with multiple challenges that can be a limiting factor to their growth and quality service delivery: These challenges are listed though not exhaustive as Technological Disruption, Regulatory landscape, intellectual Property Issues, Economic Volatility, Limited Human resource expertise, Return on investment/High Costs: Conclusion/Recommendation: The CROs in Cameroon are required to be in compliance with the law regulating research in human subjects of 2022 and the regulations on Clinical research in Cameroon. In sub Saharan Africa CROs are aligned with the regulation enforced in their different countries. The success of CROs is based on their compliance to innovative trends in clinical research and the capacity to strengthen collaboration among policy makers and actors. The ability to face challenging opportunities in clinical research and embrace transformative breakthroughs that can bring faster new chemical entities to the market at the same time improving the standard of care (SOC) of the population. In the future, the synergy between innovation, strategic partnerships, and a commitment to excellence for CROs  shall be the cornerstones of future success in conducting clinical research for Pharmaceutical drug discovery and development  Based on the regulatory demanding nature of clinical regulation in Cameroon  CROs must have a  legal jurisdiction and recognition of their operation, and conform to the norms and standard laid down by regulatory authorities and the states of their jurisdiction CROs offer a wide range of services to support the development and execution of clinical trials, ensuring compliance with regulatory requirements and ethical standards. Clinical Research Organizations (CROs) play a pivotal role in the pharmaceutical, biotechnology, and medical device industries as a research service delivery provider on a contract basis.